Phase II trial of pirfenidone in children and young adults with neurofibromatosis type 1 and progressive plexiform neurofibromas. Issue 9 (22nd April 2014) - Widemann, Brigitte C.; Babovic‐Vuksanovic, Dusica; Dombi, Eva; Wolters, Pamela L.; Goldman, Stewart; Martin, Staci; Goodwin, Anne; Goodspeed, Wendy; Kieran, Mark W.; Cohen, Bruce; Blaney, Susan M.; King, Allison; et al.
ABSTRACT Background Pirfenidone, an oral anti‐inflammatory, antifibrotic agent with activity in idiopathic pulmonary fibrosis, may mediate anti‐tumor activity in neurofibromatosis type 1 (NF1) and plexiform neurofibromas (PN) by inhibition of fibroblast proliferation and collagen synthesis. The primary objective of this open label, single arm phase II trial was to evaluate the activity of pirfenidone in children and young adults with inoperable PN. Procedure Patients (3–21 years) with NF1‐related progressive PN received pirfenidone at the previously determined optimal dose (500 mg/m2 orally, q8h) on a continuous dosing schedule (one cycle = 28 days). Volumetric MRI analysis was used to assess response. Progression was defined as ≥20% PN volume increase compared to baseline. Pirfenidone would be considered active if it doubled the median time to progression (TTP) compared to the TTP on the placebo arm of a phase II trial with the farnesyltransferase inhibitor tipifarnib, which used near identical eligibility criteria. Toxicities, objective response rate, and quality of life (QOL) also were evaluated. Results Thirty‐six patients were enrolled and tolerated pirfenidone well with intermittent nausea and vomiting as the most frequent toxicities. A dose reduction was required in only three patients. The median TTP for pirfenidone was 13.2 months compared to 10.6 months for the placebo control group from the tipifarnib trial (two‐tailed P = 0.92; one‐tailed P = 0.46). No objective responses were observed. Conclusions Pirfenidone was well tolerated, but did not demonstrate activity as defined in this trial and does not warrant further evaluation in children with NF1 and progressive PN. Pediatr Blood Cancer 2014;61:1598–1602. © 2014 Wiley Periodicals, Inc.